PEMBERDAYAAN MASYARAKAT PETANI DI KOTA PADANG - Ferrya Hamid Loedy (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aims to describe: 1) To describe the implementation of empowerment of farmer communities by the Padang City Agriculture Service. 2) To describe the inhibiting factors in the implementation of a community empowerment program by the Padang City Agriculture Service. 3) To describe solutions in overcoming the inhibiting factors in community empowerment by the Padang City Agriculture Service. This research method uses a qualitative approach with the determination of informants using purposive sampling technique. Data obtained using in-depth interviews, observation, and documentation. The results of the study show that the implementation of empowerment of farmer communities. The results of the study indicate that the form of empowerment organized by the Agriculture Service is in the form of assistance with agricultural machinery (alsintan), plant seeds, and irrigation. Assistance provided by this government in the context of self-sufficiency programs. Assistance is given to the community through farmer groups. The inhibiting factor of community empowerment consists of agricultural activities only limited to fulfilling their daily needs, still not oriented to the development of improving the welfare of farmers, farmers lack the capital and difficulties in marketing products and the difficulty of licensing. Based on the explanation above, it can be concluded that the empowerment of farming communities in the city of Padang still has several obstacles.